Decision making and restorative planning for adhesively restoring endodontically treated teeth: An update - Vidhi Kiran Bhalla; Sherin Jose Chockattu; Shyambhavi Srivastava; Sathya Prasad (Wolters Kluwer Medknow Publications, 2020)
Restoration of pulpless teeth presents a clinical challenge and a controversial topic of debate even today. The preservation of coronal tooth structure is crucial for clinical success and for maintaining biomechanical, adhesive, functional, and esthetic balance. The advent of adhesive dentistry and advancement in dental materials have resulted in mechanical properties close to the dental tissues, thereby offering a conservative treatment option to restore, reinforce, and protect endodontically treated teeth (ETT). Directly bonded restorations are indicated for teeth with the minimal loss of coronal tooth structure and can be considered effective for short-term success of root canal treated teeth. However, indirect restorations could be considered for the strengthening of the tooth with moderate loss of tooth structure, following the adequate adhesive protocols. The present review assesses literature on direct versus indirect adhesive restorations such as endocrowns, adhesive onlays, and overlays for restoring ETT. Furthermore, the article attempts to present clinical guidelines and decision-making for restoring endodontically treated anterior and posterior teeth.